2013
DOI: 10.4028/www.scientific.net/amr.718-720.1878
|View full text |Cite
|
Sign up to set email alerts
|

Change Rule of Blasting Vibration Peak Velocity in Brick-Concrete Building

Abstract: In this paper, the background is Qingdao Cross-harbor Tunnel Guide Line Project. The research on blasting vibration peak velocity was carried out by monitoring a 6-layer brick-concrete building. According the research, we discover that vibration peak velocity in the vertical direction reaches a maximum on the roof of the building. In the horizontal radial and tangential horizontal direction, the maximum appears at the 1st or 2nd floor. Third, within certain distance from blasting center, the value of horizonta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Hydrolysis is used to release protein-bound targets. Some reports [8,9,16,17] showed that MQCA could be extracted from the matrix with the help of acid hydrolysis, alkaline hydrolysis or enzymatic digest. Alkaline hydrolysis required special cautions and pH needs to be adjusted to acidic after hydrolysis; enzymatic digests need more time (about 16 h) than other methods.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Hydrolysis is used to release protein-bound targets. Some reports [8,9,16,17] showed that MQCA could be extracted from the matrix with the help of acid hydrolysis, alkaline hydrolysis or enzymatic digest. Alkaline hydrolysis required special cautions and pH needs to be adjusted to acidic after hydrolysis; enzymatic digests need more time (about 16 h) than other methods.…”
Section: Sample Preparationmentioning
confidence: 99%